Perfil neuropsicológico das paralisias cerebrais: hemiplégica e diplégica - Patricia Martins de Freitas (2009)
Recently, an expressive amount of research is been conducted in order to built explicative models concerning the cognitive development of early brain injured children. The cognitive neuropsychological pattern can be studied by comparing the performance of verbal and non verbal functions. In this sense it is possible to investigate the performance patterns as well as other phenomena frequently addressed in the literature: neuroplasticity, equipotentiality and hemispheric specialization. In this context, this thesis aims to investigate the convergence between the clinical profile and the cognitive pattern of hemiplegic and diplegic cerebral palsy (CP), addressing the linguistic and visuospatial outcomes. This focus of investigation was defined considering the most frequent patterns observed on the clinical context. CP is a clinical condition characterized by its fuzzy sintomathology, but some of its symptoms are often observed, specially communicational and motor disabilities, as well as behavioral problems. The thesis is structured in three independent studies presented in article format. The three studies represent the use of complementary methodologies to sustain the empirical evidences found. The methods, as well as the theoretical model, are based on the perspective of cognitive neuropsychology. The objective of the first study was to construct instruments to assess verbal functions. The first step of this study was the development of a Neuropsychological Assessment Battery for Lexical Processing. (NABLP). This battery contains linguistics tasks, which assess different components of the cognitive neuropsychological model of lexical processing. The results of this study showed satisfactory internal consistency and construct validity of NABLP, contributing for future studies and for clinical practice of pediatric neuropsychology. The second study was developed through a group comparison methodology, analyzing the performance on linguistic and visuospatial abilities of normal, diplegic and right and left hemiplegic children. The focus of the study was to show evidences supporting differences on the cognitive outcomes between the groups. The study was conducted analyzing the performance accuracy on the linguistic and visuospatial tasks. In this sense the aim of the study was to verify the utility of the cognitive neuropsychological model of lexical processing concerning the neuropsychological assessment in CP children, investigating the possible linking with the diagnostic classification. The results of this study showed that the linguistic impairments of children with CP are subtle, with no significant differences from the control group. However, when comparison was within the CP groups, significant alterations were found especially on hemiplegic children. As the left hemiplegic and the diplegic children were more similar to the control group, it is possible to emphasize specific linguistic deficits in children with right hemiplegia. The third study is complementary to the second one. Through cluster analysis it was possible to confirm the distinction by performance patterns between the groups. The result of the cluster analysis was important to reinforce the debate presented on the second study concerning hemispheric specialization and cerebral equipotentiality. The results found on both studies show that one cognitive profile of right hemiplegic children is an outcome of functional neuroplasticity mechanisms. The low scores on linguistic and visuospatial tasks in this group support the hipothesis of cerebral crowding. This phenomenon is typically observed when language, rather then non verbal functions, is instantiated in the right hemisphere for compensational proposes. Therefore visuospatial functions can be impaired. The results of cluster analysis support the identification of dissociated cases concerning cognitive performance. Single case study is the golden standard methodology in cognitive neuropsychology. The single case study presented is an evidence of double dissociation between linguistic and visuospatial functions. This result supports the hypothesis of hemispheric specialization, showing that the left hemisphere is more dedicated to linguistic functions while the right hemisphere is more dedicated to visuospatial ones. Overall, the results of the thesis show that hemiplegic and diplegic CP have heterogenic profiles. The cognitive profile of right hemiplegic children depend on neurocognitive reorganization processes resulting in cerebral crowding, or maintaining the pattern of hemispheric specialization observed in adults. For the children with left hemiplegia the cognitive pattern is characterized by non verbal deficits, such as visuospatial ones. Other results of the present study show that diplegic children have a heterogenic profile and for the majority of the cases the performance was similar to the one found in the control group. The results evidence the utility of cognitive neuropsychology to investigate cognitive processes. Besides the historical emphasis on single case study as the unique methodology for cognitive neuropsychology, the present thesis was able to demonstrate the importance of the complementary methodology between single case and group studies. Finally the results show that equipotentiality and hemispheric specialization are important phenomena during cognitive development. The coexistence of these properties is a result of neuronal plasticity and the connexionistic organization of the brain, contrary to the modularistic perspective